EVALUATION OF FRF PATTERNS OF VIBRATION RESPONSE AT NEW ROLLING BEARING - MONHENDRI (NIM : 13105134); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, RIKO
Rolling bearing is a common bearing used in industry. industrial machinery condition, can be monitored using vibration base predictive maintenance method. There are two important things in this method those are, frequency spectrum analysis and control trip based on the RMS measured. In many measurement result, floor noise contributed to the increase in RMS. floor Noise found in the frequency spectrum of rolling bearings resembles the pattern obtained from the FRF measurements. This study is made to evaluate the FRF patterns recorded in response to the new rolling bearing vibration. This research is started by measuring FRF of the structure as well as the bearing housing. Then, it is followed by measuring the frequency spectrum at various speed and static load. Both measurements are performed to determine whether there is a relationship between the results of these measurements. Frequency spectrum measurement results indicate a pattern resembling the results of the FRF measurement noise floor, caused by rolling friction phenomena which generate signals that are random excitation along the frequency span. Since the friction forces is proportional to normal force from the given loading, the greater static load given, the greater the FRF pattern was also recorded at the noise floor.